Colonialism in Greenland : tradition, governance and legacy - Rud, Søren (Cambridge imperial and post-colonial studies series., 2017)
This book explores how the Danish authorities governed the colonized population in Greenland in the nineteenth and twentieth centuries. Two competing narratives of colonialism dominate in Greenland as well as Denmark. One narrative portrays the Danish colonial project as ruthless and brutal extraction of a vulnerable indigenousness people; the other narrative emphasizes almost exclusively the benevolent aspects of Danish rule in Greenland. Rather than siding with one of these narratives, this book investigates actual practices of colonial governance in Greenland with an outlook to the extensive international scholarship on colonialism and post-colonialism. The chapters address the intimate connections between the establishment of an ethnographic discourse and the colonial techniques of governance in Greenland. Thereby the book provides important nuances to the understanding of the historical relationship between Denmark and Greenland and links this historical trajectory to the present negotiations of Greenlandic identity.